The Multinational Corporation and Industrial Relations : The European Approach - Malles, Paul (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
The author considers whether the multinational corporation constituted a challenge to the industrial relations systems as they have developed in Europe over the last quarter of a century and what response such a challenge found in the trade-union movement.